Activation of ABA Receptors Gene GhPYL9-11A Is Positively Correlated with Cotton Drought Tolerance in Transgenic Arabidopsis - Liang, Chengzhen; Liu, Yan; Li, Yanyan; Meng, Zhigang; Yan, Rong; Zhu, Tao; Wang, Yuan; Kang, Shujing; Ali Abid, Muhammad; Malik, Waqas; Sun, Guoqing; Guo, Sandui; et al. (Frontiers in Plant Science, 2017)
The sensitivity to abscisic acid (ABA) by its receptors, pyrabactin resistance-like proteins (PYLs), is considered a most important factor in activating the ABA signal pathway in response to abiotic stress. However, it is still unknown which PYL is the crucial ABA receptor mediating response to drought stress in cotton (Gossypium hirsutum L.). Here, we reported the identification and characterization of highly induced ABA receptor GhPYL9-11A in response to drought in cotton. It is observed that GhPYL9-11A was highly induced by ABA treatment. GhPYL9-11A binds to protein phosphatase 2Cs (PP2Cs) in an ABA-independent manner. Moreover, the GhPYL-11A-PP2C interactions are partially disrupted by mutations, proline (P84) and histidine (H111), in the gate-latch region. Transgenic Arabidopsis overexpressing GhPYL9-11A plants were hypersensitive to ABA during seed germination and early seedling stage. Further, the increased in root growth and up regulation of drought stress-related genes in transgenic Arabidopsis as compared to wild type confirmed the potential role of GhPYL9-11A in abiotic stress tolerance. Consistently, the expression level of GhPYL9-11A is on average higher in drought-tolerant cotton cultivars than in drought-sensitive cottons under drought treatment. In conclusion, the manipulation of GhPYL9-11A expression could be a useful strategy for developing drought-tolerant cotton cultivars.